The Essence of Taxes and Tax Control - Kuziyev Ravshan Ramazonovich (International Journal on Integrated Education, 2022)
The essence of taxes as the main source of the budget revenue is considered. The definition of the concept of “tax control” is proposed. The foreign experience in the field of tax control is analyzed and the directions of increasing the effectiveness of its application in the Uzbekistan are presented.